Zinc migration into liver pâté and pâté with ham packaged in black colored polypropylene containers. (September 2019) - Petrovic, Z; Lakicevic, B; Nastasijevic, I; Milicevic, D; Spiric, D; Nikolic, D
Abstract: The European food contact legislation requires verification of compliance for migration of substances from plastics food contact materials with both overall and specific migration limits. To do so in this study, migration tests were carried out using food simulant and food under well specified time and temperature conditions. A total of 28 samples of liver pâté or pâté with ham packaged in black polypropylene containers were examined for the presence of Zn according to Serbian regulation after 14 months' storage from their production dates, and data were compared to results obtained by testing empty, unused containers according to EU legislation. Elevated Zn concentrations of 161.27-327.54 mg/kg (above the maximum prescribed limit of 100 mg/kg) were registered in pâté from zones in contact with the polypropylene packaging, while pâté in zones not in contact with packaging had lower Zn levels (9.98-15.08 mg/kg).